Factors limiting plant recruitment in a tropical Afromontane Forest. (23rd November 2022) - Abiem, Iveren; Dickie, Ian; Kenfack, David; Chapman, Hazel M.
Abstract: Predicting how forest species composition may change in response to global change is essential for meaningful management. Which species are most likely to successfully recruit depends on a multitude of factors, but processes operating at the seed‐to‐seedling transition being especially important. Here, we explore how insufficient seed dispersal (dispersal limitation) and ecological filtering of seedlings (establishment limitation) influence species recruitment in an Afromontane Forest. We combined census data from seeds in seed traps and seed‐seedling transition plots in a Nigerian montane forest to measure dispersal and establishment limitation across species, life history strategies, and seed sizes. From 106 seed traps and 318 seedling plots, we recorded 11, 278 seeds from 38 species and 2688 seedlings of 61 species. All species except for one liana showed strong dispersal limitation while 23 out of the 30 species showed establishment limitation. The two lianas sampled had significantly lower dispersal limitation compared to the trees investigated in the study. Our results suggest that both dispersal and establishment limitation are markedly high in this Afromontane forest than would be expected in a lowland counterpart. Abstract : Which species are most likely to successfully recruit depends on a multitude of factors, but with processes operating at the seed‐to‐seedling transition being especially important. In this study, we explore how insufficient seed dispersal (dispersal limitation) and ecological filtering of seedlings (establishment limitation) influence species recruitment in an Afromontane Forest. Our results suggest that both dispersal and establishment limitation are markedly high in this Afromontane Forest than would be expected in a lowland counterpart.